Réponses

2014-05-19T20:32:12+02:00
Enlever les parenthèses et réduire:

a= 3a + 5 - (2a + 7) + (8 - 5a)

a= 3a + 5 - 2a - 7 + 8 - 5a 

a= 3a - 2a - 5a + 5 - 7 + 8

a= -4a + 6

b= -b + 4 + (3b - 2) - (8b - 5)

b= -b + 4 +  3b - 2 - 8b + 5

b= -b + 3b - 8b + 4 - 2 + 5

b= -6b + 7

c= 6 - 5c + 3c - (4 - 6c) + 5 + (7 - 2c)

c= 6 - 5c + 3c - 4 + 6c + 5 + 7 - 2c

c= -5c + 3c + 6c - 2

c + 6 - 4 + 5 + 7

c= 2c + 14

d= d- 1 - (3d + 4) + (5 - 4d) - (7d + 5) + 5

d= d - 1 - 3d - 4 + 5 - 4d - 7d - 5 + 5

d= d - 3d - 4d - 7d - 1 - 4 + 5 - 5 + 5

d= -13d + 0

d= -13d
  • Utilisateur Brainly
2014-05-19T20:33:15+02:00
Bonjour, 

Réduire : 

A= 3a + 5 - 2a + 7 + 8 - 5a
A= 3a - 2a - 5a + 5 + 7 + 8
A= - 4a + 20

B= - b + 4 + 3b - 2 - 8b - 5
B= - b + 3b - 8b + 4 - 2 - 5
B= - 6b - 3

C= 6 - 5c + 3c - 4 - 6c + 5 + 7 - 2c
C= - 5c + 3c - 6c - 2c + 6 - 4 + 5 + 7
C= - 10c + 14

D= d - 1 - 3d + 4 + 5 - 4d - 7d + 5 + 5
D= d - 3d - 4d - 7d - 1 + 4 + 5 + 5 + 5
D= - 13d - 17 

Bonne soirée! =)